Phytochemical Analysis of The Leaves, Roots, Stems, and Stem Bark of the Bengkal Plant (Nauclea subdita) - Pitri, Rosiana; Masriani; Eka Kusuma Wardani; Kurniawan, Hengki; Rafif, Muhammad; Nabila, Chesya (Universitas Pendidikan Mandalika, 2025)
Bengkal (Nauclea subdita (Korth.) Steud) is a medicinal plant that has been traditionally used for various treatments and is known to contain a wide range of secondary metabolites. However, most previous studies have focused only on the leaves, so information regarding the phytochemical composition of other plant parts remains very limited. This research is important to provide a comprehensive overview of the bioactive contents in all morphological parts of N. subdita, which have the potential to support the development of biological and pharmacological applications, such as antibacterial, antioxidant, antidiabetic, and anticancer activities commonly associated with alkaloids, flavonoids, and phenolic compounds. Secondary metabolite analysis was conducted on the leaves, roots, stems, and bark using phytochemical screening. Samples were collected from Ketapang, West Kalimantan, then dried, ground, and extracted using sequential maceration with n-hexane and ethanol. The extracts were subsequently fractionated with dichloromethane (DCM) at pH 3 and pH 9. Moisture content was determined using the gravimetric method. Phytochemical screening was carried out using standard qualitative tests, including Mayer’s and Wagner’s tests for alkaloids, color tests for flavonoids and phenolics, the Liebermann–Burchard test for triterpenoids, the FeCl₃ test for tannins, and the foam test for saponins. The results showed that all parts of the plant contain alkaloids, flavonoids, phenolics, and triterpenoids, although there were variations among extracts and fractions. Tannins were detected only in the leaves, while saponins were found in the leaves, roots, and stems. These findings confirm that all parts of N. subdita possess important biological potential due to the presence of major bioactive compounds that play a role in the development of herbal medicines and nature-based therapeutic agents. This information serves as a significant initial foundation for further pharmacological research.